2020
DOI: 10.21203/rs.3.rs-57104/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac involvement in COVID-19 patients: mid-term follow up by cardiac magnetic resonance imaging

Abstract: Background: Coronavirus disease 2019 (COVID-19) induces myocardial injury, either direct myocarditis or indirect injury due to systemic inflammatory response. Myocardial involvement has been proved to be one of the primary manifestations of COVID-19 infection, according to laboratory test, autopsy, and cardiac magnetic resonance imaging (CMRI). However, the middle-term outcome of cardiac involvement after the patients were discharged from the hospital is yet unknown. The present study aimed to evaluate mid-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…We found that cardiac involvement, including RV systolic dysfunction, segmental LV deformation decrease, myocardial edema and fibrosis were not uncommon even after six months of recovery. Findings in our study was consistent with and a supplement to previous researches in early convalescence [3] , [4] , [5] , [6] , [7] , [8] . Abnormal findings in COVID-19 survivors after 110 days and 6 months imply continuous inflammation, which may be the reason for the lasting cardiac involvement in our patients [ 1 , 2 ].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…We found that cardiac involvement, including RV systolic dysfunction, segmental LV deformation decrease, myocardial edema and fibrosis were not uncommon even after six months of recovery. Findings in our study was consistent with and a supplement to previous researches in early convalescence [3] , [4] , [5] , [6] , [7] , [8] . Abnormal findings in COVID-19 survivors after 110 days and 6 months imply continuous inflammation, which may be the reason for the lasting cardiac involvement in our patients [ 1 , 2 ].…”
supporting
confidence: 92%
“…), impaired pulmonary function, abnormal chest CT images in COVID-19 survivors even after 110 days and 6 month of follow-up [ 1 , 2 ]. Several studies also have reported that cardiac involvement, including myocardial edema, fibrosis, and cardiac dysfunction, detected by using multi-parameter cardiac magnetic resonance (CMR) techniques were identified in recovered COVID-19 patients during early convalescence [3] , [4] , [5] , [6] , [7] , [8] . However, whether COVID-19 has a continuous influence on the cardiovascular system in late convalescence is unknown.…”
mentioning
confidence: 99%